Analysis of the Relationship between Neutrophil-Lymphocyte Ratio (NLR) Values and Body Mass Index in Tuberculosis Patients - Wahyu Nurfiyana; A. Zakaria Amien (Poltekkes Kemenkes Tanjung Karang, 2026)
Tuberculosis (TB) is a communicable infectious disease that remains a major public health problem, particularly in Indonesia. Low nutritional status can impair immune function and worsen the clinical course of TB. Body Mass Index (BMI) is commonly used to measure nutritional status. In contrast, the neutrophil–lymphocyte ratio (NLR) is a simple inflammatory biomarker reflecting the balance between innate and adaptive immune responses. This study aimed to analyze the relationship between NLR and BMI among TB patients undergoing treatment. This cross-sectional study involved 32 tuberculosis patients receiving treatment at Puskesmas Sukabumi, Bandar Lampung. NLR values were obtained from blood tests using a hematology analyzer and calculated as the neutrophil count divided by the lymphocyte count. BMI was determined from body weight and height measurements. Statistical analysis included Spearman's correlation test to examine the relationship between NLR and BMI, and a One-Way ANOVA to assess differences in NLR across BMI classifications. The results showed that the mean BMI was 20.4±3.0 kg/m², and the median NLR was 2.7. A significant negative correlation was found between BMI and NLR (r = -0.379; p = 0.03), indicating that lower BMI was associated with higher NLR. Significant differences in NLR were also observed among BMI categories (p = 0.003), with underweight subjects demonstrating the highest NLR values. These findings suggest a relationship between nutritional status and systemic inflammatory responses in TB patients. BMI and NLR may serve as simple indicators for assessing inflammatory status and monitoring treatment progress in tuberculosis patients.